Construction solutions for historical object foundations in the context of changing their functional use = Rozwiązania konstrukcyjne posadowień obiektów zabytkowych w kontekście zmiany ich funkcji użytkowej - Gwizdała, Kazimierz; Florkowska, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Properly executed renovation and adaptation of a grade listed property not only ensures its constructional safety, but may also highlight the object?s historical value. Taking into consideration various factors, such as divergence of interests, or technical and legal determinants, it is safe to say that the renovation and adaptation of grade listed properties for new purposes is a complex process.
Keywords: obiekty zabytkowe; renowacja; zmiana funkcji użytkowej; wzmacnianie fundamentów; iniekcja strumieniowa; historical objects; changing functional of use; renovation; reinforcement of foundations; jet grouting